RESEARCH OF INFLUENCING OF PROJECT DISCRIPTIONS OF ELEVATOR ON PARAMETERS OF ITS DRIVE - Bohomaz, V. M.; Hlavatskyi, K. Ts.; Mazur, O. A. (Science and Transport Progress, 2015)
Purpose.One of basic elements of band bucket elevators is their drive. For determination of power drive it is necessary to conduct calculations on standard by methods, in what it is needed to expend enough time. One of project parameters is productivity of elevator. It is necessary to build parametric dependence of power drive of elevator on its design capacity that takes into account a type and descriptions of load, lifting height, standard sizes and parameters of buckets and tapes. Methodology. Using the method of hauling calculation of band buckets elevators, the parametric dependences of power drive of high-speed elevators are built with deep and shallow buckets from their productivity at fixed type of load and height of getting up. Findings.It is set on the basis of the built parametric dependences that the change function of a size of elevator power from design capacity (at fixed to the lifting height, load type, rate of tape movement) is piecewise and droningly increasing. The intervals of project values of productivity, which provide the permanent size of elevator power drive are certain in a general view. As the example of application of the recived results the construction process of power drive dependence from design capacity of elevator of shotblasting room, which is intended for transporting of the metallic shot using for consolidating of carriage springs, is considered. For concrete type of load and lifting height of such elevator graphic dependence of power drive on productivity was built. Originality.Parametric dependences of elevator power drive on its design capacity were first built, which take into account a type and physical and mechanical descriptions of load, lifting height, standard sizes and parameters of buckets and tapes. Practical value. The use of the built dependences enables in relation to rapid determination of approximate value of power drive of vertical high-speed elevators with deep and shallow buckets on the stage of planning and to execute the high-quality selection of its basic elements at concrete project descriptions: type of load, productivity, lifting height.